2010
DOI: 10.1186/1471-2474-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of elective total joint replacement in persons with end-stage knee osteoarthritis

Abstract: BackgroundArthritis is a leading cause of disability in the United States. Total knee arthroplasty (TKA) has become the gold standard to manage the pain and disability associated with knee osteoarthritis (OA). Although more than 400 000 primary TKA surgeries are performed each year in the United States, not all individuals with knee OA elect to undergo the procedure. No clear consensus exists on criteria to determine who should undergo TKA. The purpose of this study was to determine which clinical factors will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 38 publications
4
115
1
1
Order By: Relevance
“…Prior studies [2,3,20,21,26] have demonstrated an association between K-L grade and the presence and severity of chondral damage and symptoms of OA in the knee on MR images. A few studies [7,23] have used the K-L grading system to evaluate hips.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies [2,3,20,21,26] have demonstrated an association between K-L grade and the presence and severity of chondral damage and symptoms of OA in the knee on MR images. A few studies [7,23] have used the K-L grading system to evaluate hips.…”
Section: Discussionmentioning
confidence: 98%
“…13 Studies have found that women are less likely to undergo TJR than men, 14 and younger individuals with a full knee range of motion are less likely to undergo total knee replacement (TKR). 15 There is little published research investigating the biomedical and psychosocial differences between patients who are referred in primary care by the GP and those who are considered candidates for a TJR. This study set out to investigate differences between individuals with OA newly referred to an orthopaedic surgeon for consideration for TJR; to identify differences in individuals who were put on the waiting list for TJR; and to identify the predictors of having a THR or TKR.…”
Section: Introductionmentioning
confidence: 99%
“…BLOKS and WORMS scoring systems were presented with their three separate scores for the cartilage, bone marrow and meniscus. As mentioned above, following previous studies [18][19][20], the risk of (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) are also similarly used in Tables 3, 4 and 5 for further analysis subsequent KR was calculated per every one unit increase in the average scores of all locations (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The chronic and often progressive clinical course of knee OA emphasizes the role for possible preventive strategies in early detection and secondary prevention of endstage joint destruction requiring KR. Recent studies have focused on extracting the predictors of the development and progression of OA for accurate outcome prediction of painful knee OA with possible ensuing joint replacement [4,[7][8][9]. Several well-defined cohorts have been initiated for this purpose, such as osteoarthritis initiatives (OAIs), the Multicentric Osteoarthritis Study (MOST) and Framingham Osteoarthritis Study [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%